Synthesis and Complexation of Monotosylated 4-Aminopyridine with Nickel (II) and Iron (II) Ions - Orie, Kingsley John; Duru, Remy Ukachukwu; Ngochindo, Raphael I-oro (UI Scholars Hub, 2021)
Tosylated 4-aminopyridine and other sulfonylated compounds of amines comprise a substantial class of pharmaceutical drugs used as antibiotics in the field of medicine. This research aimed at the synthesis of tosylated 4-aminopyridine and the complexation of the tosyated 4-aminopyridine with Ni(II) and Fe(II) ions. The sulfonamide was prepared by the action of tosyl chloride on 4-aminopyridine in an aqueous alkaline medium. The complexes were synthesized by the reaction of Ni(NO3)2.6H2O /Fe(NO3)2.6H2O with sulfonamide derivative. These compounds were characterized through Ultraviolet Visible spectroscopy (UV–Vis), Fourier Transform Infer-Red (FTIR) spectroscopy, Proton Nuclear Magnetic Resonance (1HNMR), Carbon-13 Nuclear Magnetic Resonance (13CNMR) and Electron Spray Ionisation-Mass Spectrometer (ESI-MS) and micro-analysis. The IR spectral data suggested that the sulfonamide derivative acts as a neutral ligand towards Ni (II) and Fe (II). In their complexes, the coordination frequency bands of 1665.55 and 1674.21 cm−1 were assigned to Ni−N and Fe−N bonds, and 1687.70 cm−1 was assigned to free tosylated 4-aminopyridine. This decrease in the frequency band of free imine to coordinated imine complexes indicates that electron transfer occurred from the ligand to the d-orbitals of the metals. The complexation of4-Methyl-N-(pyridin-4-yl)benzene sulfonamide can increase the biological and catalytic potential of the ligand in the pharmaceutical and chemical industries.